Transplanting interventions could help conserve the living fossil Athrotaxis cupressoides under fire regimes induced by climate change - French, Ben J.; Prior, Lynda D.; Bowman, David M. J. S. (Frontiers in Conservation Science, 2024)
IntroductionPencil pine (Athrotaxis cupressoides) is an iconic, paleoendemic tree restricted to historic fire refugia in Tasmania’s western mountains. Anthropogenic climate change is increasingly exposing these areas to wildfire. Given that pencil pines have little capacity to recover from fire, and show scarce natural recruitment across their core range, they will be lost from many areas without interventions to restore population viability to burnt stands.MethodsWe conducted a large-scale field study targeting pencil pine stands burnt in recent (2016) and historic (1960) fires. Using small (0.5 m2) experimental plots distributed across a range of topography and vegetation, we trialled three interventions: i) protecting groups of naturally germinated seedlings from herbivores in situ (35 plots); ii) introducing seeds via multiple sowing methods (300 plots); and iii) transplanting tube stock propagated from seed or cutting material, with and without herbivore protection (1007 plots).ResultsWe found that protecting natural germinants from herbivores did not prevent seedling mortality over 2.5 years, and sowing interventions largely failed. Most transplants exposed to herbivores failed to establish after 1.5 years, but establishment rates were high with herbivore exclusion, indicating strong predation by native macropod herbivores. Transplant establishment also varied with fine-scale topography, with the best outcomes in well-drained and Sphagnum dominated positions, and the worst outcomes in poorly-drained positions, suggesting young pencil pines are sensitive to waterlogging. Transplant establishment rates varied little between recently and historically burnt sites, and were insensitive to how plants were propagated.DiscussionIn summary, transplanting tube stock with herbivore protection is a promising method for restoring burnt pencil pine stands, and establishment rates can be improved by selecting favourable planting positions at fine scales. Our findings suggest pencil pine stands burnt decades previously are suitable for restoration. Managers seeking to conserve pencil pines may begin restoring both historically and recently burnt stands, alongside protecting unburned stands from fire. Interventions should be refined through adaptive management, including re-surveys of this long-term trial.